Climate-Smart Drip Irrigation with Fertilizer Coupling Strategies to Improve Tomato Yield, Quality, Resources Use Efficiency and Mitigate Greenhouse Gases Emissions - Xinchao Ma; Yanchao Yang; Zhanming Tan; Yunxia Cheng; Tingting Wang; Liyu Yang; Tao He; Shuang Liang (Land)
Background: Integrated water and fertilizer management is important for promoting the sustainable development of agriculture. Climate-smart drip irrigation with fertilizer coupling strategies plays an important role to mitigate greenhouse gas emissions, ensuring food production, and alleviating water scarcity and excessive use of fertilizers. Methods: The greenhouse experiment consists of three drip irrigation treatments which include D1: drip irrigation (100 mm); D2: drip irrigation (200 mm); D3: drip irrigation (300 mm) under three different fertilizer management practices N1: nitrogen level (150 kg N ha−1); N2: nitrogen level (300 kg N ha−1); N3: nitrogen level (450 kg N ha−1). Results: The results showed that significantly improved soil moisture contents, quality and tomato yield, while reduced (38.6%) greenhouse gas intensity (GHGI) under the D3N3 treatment. The D2 and D3 drip irrigation treatments with 450 kg nitrogen ha−1 considerably improved NH4+-N contents, and NO3−-N contents at the fruit formation stage. The improve in net primary productivity (NPP), net ecosystem productivity (NEP), evapotranspiration (ET), and ecosystem crop water productivity (CWPeco) through D3N3 treatment is higher. The D3N3 treatment improved (28.2%) the net global warming potential (GWP), but reduced GHGI, due to improved (18.4%) tomato yield. The D3N3 treatment had significantly greater irrigation water productivity (IWP) (42.8%), total soluble sugar (TSS) (32.9%), vitamin C content (VC) (39.2%), soluble sugar content (SSC) (44.2%), lycopene content (41.3%) and nitrogen use efficiency (NUE) (52.4%), as compared to D1N1 treatment. Conclusions: Therefore, in greenhouse experiments, the D3N3 may be an effective water-saving and fertilizer management approach, which can improve WUE, tomato yield, and quality while reducing the effect of global warming.